Differential Aeromonas hydrophila resistance mechanisms of Megalobrama terminalis and Megalobrama amblycephala revealed by quantification proteomics - Fang Xianping; Zhu Limin; Liu Kai; Ruan Songlin; Xu Baoqing; Xie Nan; Cai Lijuan; Liu Xinyi; Dai Yulai; Feng Xiaoyu; Li Zhongquan (浙江大学学报. 农业与生命科学版, 2015)
Bacterial sepsis is a serious infection for fish. In the past years, the feeding cost of Megalobrama amblycephala had been seriously affected by bacterial sepsis. However, bacterial sepsis does not extensively occur during the feeding processes of Megalobrama terminalis. Therefore, M. terminalis which is highly resisted to bacterial sepsis is increasingly favored by farmers.To study the pathogen resistance mechanism of different varieties of Megalobrama fish in response to Aeromonas hydrophila, we used label-free based proteomics technology to study the proteome change of the livers of M. terminalis and M. amblycephala infected with A. hydrophila at 0 h, 3 h, 10 h and 24 h.After identification and relative quantification, 49 and 29 proteins changed at different post-infection time points in M. terminalis and M. amblycephala, respectively. The differentially expressed proteins were deeply analyzed by gene ontology annotation and bioinformatics, and we found that, by comparing with M. amblycephala, the percentage of differentially expressed redox proteins in M. terminalis increased from 7% to 13%, and β-globin was up-regulated (1.66, 3.44 and 1.93 times increased at 3 time points). Furthermore, we found that M. terminalis may specifically induce synergistic pathogen resistance mechanism including the regulation of pentose phosphate pathway, metabolism of fatty acids, leucine metabolism pathway and over-expression of β-globin to resist the invasion of pathogens.In summary, we studied four different stages of Megalobrama liver proteome expression after A. hydrophila infection, and found different pathogen resistance signal response pathway between two fish species, which indicates the resistance mechanism of different fish species after A. hydrophila infection. The result is of great benefit to further deeply reveal the molecular mechanisms of fish pathogen interactions and the breeding of pathogen-resistant Megalobrama fish varieties.